The safety of modafinil in combination with oral Δ9-tetrahydrocannabinol in humans - Sugarman, Dawn E. (2010)
Marijuana (cannabis) is the most widely used illicit substance globally, and cannabis use is associated with a range of adverse consequences. Currently, no medications have been proven to be effective for the treatment of cannabis addiction. The goals of this study were to examine the safety and efficacy of a potential treatment medication, modafinil, in combination with oral Δ9-tetrahydrocannabinol (THC). Twelve male and female occasional cannabis users participated in an outpatient double-blind, placebo-controlled, crossover study. Across four sessions, participants were randomly assigned to a sequence of four oral treatments: (1) 400 mg modafinil + placebo, (2) 15 mg THC + placebo, (3) 400 mg modafinil + 15 mg THC, or (4) placebo + placebo. Outcome measures included heart rate, blood pressure, performance on the Rapid Visual Information Processing (RVIP), and the Hopkins Verbal Learning Test (HVLT), and subjective measures. Oral THC increased heart rate, and produced increased subjective ratings of feeling “high” and “sedated,” as well as increased ratings of euphoria. Modafinil alone increased the Profiles of Mood States (POMS) subscales of vigor and tension. These findings support the safety of modafinil in combination with THC. The effects of modafinil in combination with a range of doses of THC need to be determined in future studies.